PENGARUH MODEL PEMBELAJARAN POE2WE BERBANTUAN PHET SIMULATIONS PADA MATERI CAHAYA DAN ALAT OPTIK TERHADAP KETERAMPILAN BERPIKIR KRITIS - Latifah, Fitriana; Rakhmawan, Aditya; Wahyuni, Eva Ari; Ahied, Mochammad; Yamin, Yamin (Natural Science Education Research, 2023)
This study aimed to determine the influence of POE2WE model with PhET Simulations on student’s critical thinking skills in learning light and optical instrument. The sample used was the VIII A as the experimental class and VIII B as the control class. The method used on this study is quantitative method with quasi experimental type and the design is nonequivalent control group design. This research was conducted at SMP Negeri 2 Welahan for the 2022/2023 Academic Year. Data collection instruments on this study is critical thinking skills test. The results of this study showed that there is an influence of POE2WE model with PhET Simulations on student’s critical thinking skills prove by increased in critical thinking skills on both class in the moderate category with n-gain score 0,64 for the experimental class and 0,41 for the control class.